Implementation of the Canva-Based Picture and Picture Learning Model in Social Studies Learning for Grade V Students of SD Negeri 22 Lubuklinggau - Helia Fitra; Tio Gusti Satria; Tidi Maharani (Jurnal Profesi Pendidikan, 2025)
This study aims to determine the completeness of social science (IPS) learning outcomes of fifth-grade students of SD Negeri 22 Lubuklinggau, after the implementation of the Canva-based picture and picture learning model. The background of this study is based on the low criteria for achieving learning objectives (KKTP) of students as indicated by the results of many tests that are still below standard. This study uses quantitative with a pre-experimental design of one-group pre-test and post-test. The population in this study were all fifth-grade students of SD Negeri 22 Lubuklinggau and the research sample was class V.A, totaling 22 students. The instrument used was a multiple-choice test that had gone through a validation process and reliability testing. The results of data analysis showed a significant increase in learning outcomes after the implementation of the Canva-based picture and picture learning model, with a significance level of α = 5% obtained t count = 4.31 and t table = 1.720 (t count < t table). These findings demonstrate that the use of interactive learning models, such as Canva-based picture and picture, can help students understand and motivate them in social studies. Therefore, it can be concluded that after implementing the Canva-based picture and picture learning model, significant improvements were achieved.